ChemInform Abstract: Progress on the Synthesis and Catalytic and anti‐Migration Properties of Ferrocene‐Based Burning Rate Catalysts. Issue 42 (September 2016) - Zhou, Weidong; Wang, Li; Yu, Haojie; Tong, Rongbai; Chen, Qing; Wang, Junhua; Yang, Xianpeng; Zain‐ul‐Abdin, Xianpeng; Saleem, Muhammad
Abstract: Review: 93 refs.